ANALISIS PERBANDINGAN MAKNA PERIBAHASA BAHASA MANDARIN-INGGRIS YANG MENGANDUNG ALAT GERAK “TANGAN”DAN“KAKI” - Alber Justine; Lily Thamrin; Lusi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Idioms are part of cultural expressions that play an crucial role in intrapersonal communication. There are many motoric organs within Chinese and English idioms. This study endeavor Chinese and English idioms that contain motor organs “hand” and “foot,” and the metaphorical meanings contained therein regarding human behavior, ability, and action. Using a qualitative technique through literature review and comparative analysis, this study unravel their emotional connotations therein similarities and differences. The result implies that in both languages, “hand” and “foot” is common embodiment of behavioral patterns, ability levels, action states, and situational conditions, Externalizing shared human physical experience. In terms of emotional nuance, Chinese idioms with “hand” are predominantly positive (44.64%), The aforementioned with “foot” are mainly negative (51.61%). In English, “hand” idioms unveil a relatively equivalent distribution between positive (37%) and negative (37.5%) meanings, whereas “foot” idioms are mostly negative (43.75%). Idioms containing both “hand” and “foot” in both languages predisposed to carry negative meanings. Overall, while Chinese and English idioms share similar metaphorical apparatus, they differ in structural manifestations and emotional tendencies, externalizing distinct cultural and cognitive patterns.